Treading on hallowed ground : counterinsurgency operations in sacred spaces - Fair, C. Christine; Ganguly, Sumit (Oxford University Press, 2008)
After America's Iraq adventure devolved into a debacle, a chorus of commentators and analysts noted that the U.S. military had no plan to fight a counterinsurgency campaign. Given the failure of conventional tactics, America in the last two years has redoubled its efforts to develop a new strategy to fight the Iraqi insurgency, and has gone so far to place our leading counterinsurgency expert, General David Petraeus, in charge of the Iraq theater. In sum, there seems to be a growing consensus that for better or worse, counterinsurgency will be a core tactic in future American military campaign.